The association of LEPR Q223R polymorphism with type 2 diabetes mellitus in Malaysia - Al-fahham, Layth Ahmed Ali; Jemon, Khairunadwa; Ab Latif, Nurriza; Abu Bakar, Suhaili; Syed Alwi, Sharifah Sakinah (Elsevier, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a major global public health problem that leads to increased risk of morbidity and mortality due to its complications. Leptin receptor plays a crucial role in regulating glucose metabolism and insulin sensitivity. Thus, mutation in the leptin receptor gene might play a role in the pathogenesis of T2DM. Objective: Our study aimed to evaluate the association of the Q223R polymorphism in the LEPR gene with Malaysian T2DM patients. Methods: A case-control study was focused on the three major ethnic groups of Malaysian population (100 Malays, 100 Chinese, and 100 Indians). Genotyping analysis of LEPR Q223R polymorphism was carried out by PCR-RFLP in 150 T2DM patients and 150 non-diabetic subjects as control. Serum insulin and leptin levels were determined using ELISA. A homeostasis model assessment-insulin resistance (HOMA-IR) and BMI were also calculated. Results: T2DM patients had significantly (P > 0.001) higher serum leptin levels as compared to the non- diabetic volunteers (166.78 pg/ml, 101.94 pg/ml, respectively). The frequency of AG genotype of LEPR Q223R variant was significantly higher in T2DM patients as compared to the control group (58.66% vs. 42%, χ2 = 8.75, p = 0.013). The A allele frequency was significantly higher in T2DM patients than the non-diabetic individuals (36.66% and 29%, respectively, P = 0.046). Furthermore, there were markedly elevated serum leptin, insulin, HOMA-IR, and BMI in diabetic patients with GG genotype of this variant as compared to AA, and AG genotypes (P < 0.05). Conclusion: Our findings demonstrated a significant association between LEPR Q223R polymorphism and T2DM in Malaysian subjects, particularly in Malay and Chinese ethnics, but not for Indian ethnic. This study suggested the A allele frequency of Q223R variant significantly increases the risk of T2DM in Malaysian population. Likewise, the polymorphism of Q223R in the LEPR gene is also associated with markedly increased serum insulin, leptin, HOMA-IR, and elevated BMI in T2DM patients.